(3EYQGH GdYhGed GdeGFIs - (3eLghds
(3ChdgG (B:s
(3GdMeO def hLH YdjfG KfGDg hdef dG jRhd ef MH GdfYe YdjfG ZfGDg hHYO aEfj deG QCjJ GdWGdHjf jWdHhf TQMG ddYhGed ddTjN GdEeGe YHO GdbGgQ dMd EYQGHgG CQOJ Cf CHjf EYQGHgG HbO WGbJjs
(3BNQgG (B:s
(3hGdhGh MQa YWa GdhVjY eQahY daXG Ydi Cfg eYWha Ydi GdcHjQ hGdhGh MQa YWa GdQajY eQahY daXG Ydi Efg eYWha Ydi GdhVjY Yf MQa LQ eYQaJgG eYQaI eLQhQIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdfMhs